The Theory and Management of Systems (Book). - Zeff, Stephen A.; Davis, Gordon B. (The Accounting Review, 1963)
Reviews the book "The Theory and Management of Systems," by Richard A. Johnson, Fremont E. Kast and James E. Rosenzweig.